Performance Investigation of OFDM-FSO System under Diverse Weather Conditions of Bangladesh - Maliha Sultana; Agnila Barua; Jobaida Akhtar; Mohammad Istiaque Reja (Institute of Advanced Engineering and Science, 2018)
Free space optical (FSO) communication systems which are deployed for last mile access, being considered as a suitable alternative technology for optical fiber networks. It is one of the emerging technologies for broadband wireless connectivity which has also been receiving growing attention due to high data rate transmission capability with low installation cost and license free spectrum. However, the widespread use of FSO technology has been hampered by the randomly time varying characteristics of propagation path mainly due to atmospheric turbulence, sensitivity to diverse weather conditions and the nonlinear responsivity of laser diode. This paper presents the performance investigation of an OFDM-FSO system over atmospheric turbulence channels under diverse weather conditions of Bangladesh. The channel is modeled with gamma-gamma distribution using 16-QAM modulation format and 4×4 multiple transceiver FSO system. All possible challenges are imposed on the system performance such as atmospheric attenuation, turbulence, pointing error, geometric loss etc. The refractive index structure parameter and atmospheric attenuation coefficient for different weather conditions are calculated by using the data, collected from Bangladesh Meteorological Department. The acquired results can be fruitful for scheming, forecasting and assessing the OFDM-FSO system’s ability to transmit wireless services over turbulent FSO links under actual conditions of Bangladesh.